2018
DOI: 10.1002/cphc.201801034
|View full text |Cite
|
Sign up to set email alerts
|

Interleaved Dual NMR Acquisition of Equivalent Transfer Pathways in TOCSY and HSQC Experiments

Abstract: A dual NMR data acquisition strategy to handle and detect two active equivalent transfer pathways is presented and discussed. We illustrate the power of this time-efficient approach by collecting two different 2D spectra simultaneously in a single experiment: i) TOCSY or HSQC-TOCSY spectra with different mixing times, ii) F2-13 C-coupled and decoupled HSQC spectra, iii) conventional and pure-shift HSQC spectra, or iv) complementary HSQC and HSQC-TOCSY spectra.The overall experimental time of a 2D NMR experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…The approach relies on the appropriate ordering of individual techniques (modules) within each supersequence to control the sequential sampling of magnetisation pools, thus yielding the required data sets for characterisation in an approach that has been termed NMR by Ordered Acquisition using 1 H detection (NOAH). The NOAH approach represents one category of techniques that employ multi‐FID acquisitions in a single concatenated experiment that are gaining recognition as time‐efficient data collection strategies . These are attractive as they can be executed using conventional spectrometer hardware without the need for multiple receivers, as used in parallel acquisition NMR spectroscopy, nor do they suffer the technical complexities associated with single‐scan ultrafast correlation methods …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The approach relies on the appropriate ordering of individual techniques (modules) within each supersequence to control the sequential sampling of magnetisation pools, thus yielding the required data sets for characterisation in an approach that has been termed NMR by Ordered Acquisition using 1 H detection (NOAH). The NOAH approach represents one category of techniques that employ multi‐FID acquisitions in a single concatenated experiment that are gaining recognition as time‐efficient data collection strategies . These are attractive as they can be executed using conventional spectrometer hardware without the need for multiple receivers, as used in parallel acquisition NMR spectroscopy, nor do they suffer the technical complexities associated with single‐scan ultrafast correlation methods …”
Section: Introductionmentioning
confidence: 99%
“…The NOAH approach represents one category of techniques that employ multi-FID acquisitions in a single concatenated experiment that are gaining recognition as time-efficient data collection strategies. [3][4][5][6] These are attractive as they can be executed using conventional spectrometer hardware without the need for multiple receivers, as used in parallel acquisition NMR spectroscopy, [7][8][9] nor do they suffer the technical complexities associated with single-scan ultrafast correlation methods. [10][11][12] Recently, we have demonstrated the NOAH BS-element as being the optimum ordering to sample HMBC (B) and HSQC (S) correlation data in a single experiment and exemplified its use in the BSC and BSCN combinations (where C signifies COSY and N NOESY).…”
Section: Introductionmentioning
confidence: 99%
“…Collecting the COSY data during the NOESY mixing time does not change the duration of the NOESY experiment, and therefore, COCONOSY can be useful in situations requiring high sample throughput. Recently, it has been shown that MFA can also be efficient in the management of the two equivalent CTPs involved in sensitivity‐enhanced gradient‐selected TOCSY and HSQC experiments . The particularities of this dual acquisition approach have been exemplified by collecting two phase‐sensitive TOCSY spectra with different mixing times at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that MFA can also be efficient in the management of the two equivalent CTPs involved in sensitivity-enhanced gradient-selected TOCSY and HSQC experiments. [8] The particularities of this dual acquisition approach have been exemplified by collecting two phasesensitive TOCSY spectra with different mixing times at the same time. Similarly, two HSQC data sets showing different features can be obtained using this time-efficient strategy.…”
Section: Introductionmentioning
confidence: 99%
“…hundreds of NOAH-type combinations are possible [11], rather fewer NOAH supersequences, including BSC, BSCN, SBC, and SBCN, provide sufficient information in a single measurement to allow computer assisted structure elucidation (CASE) [12]. Here we introduce new NOAH modules based on the principles of isotope filtering [14], preservation of equivalent coherence pathways [15,16], time-sharing [17][18][19] and multiple receiver techniques [20,21]. These enable the design of new and efficient supersequences for fast structure elucidation of small organic molecules from a single measurement in conjunction with the CASE techniques.…”
mentioning
confidence: 99%